Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/scrt532
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose-derived stromal/stem cells demonstrate short-lived persistence after implantation in both an immunocompetent and an immunocompromised murine model

Abstract: IntroductionMesenchymal cells are emerging as a promising cell platform for regenerative therapies. However, the fate of cells after transplantation in many different disease settings and tissue beds remains unclear.MethodsIn this study, human adipose-derived stromal/stem (ASCs) cells were fluorescently labeled with a membrane dye and injected into both immunocompetent and immunocompromised mouse strains. Cells were injected either as single cell suspensions, or as self-assembling spheroids. In parallel, cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 35 publications
1
37
3
Order By: Relevance
“…But it has to be stated clearly that as early as three weeks after MSC injection, DNA extracted from the HE‐positive cellular depots did not yield sufficient products by polymerase chain reactions (PCR, not shown). This is in line with recent reports indicating that injected cells can be detected only for a short period of time after application . In contrast, in our study many MSCs remained at the spot of application and wasted, possibly by factor deprivation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…But it has to be stated clearly that as early as three weeks after MSC injection, DNA extracted from the HE‐positive cellular depots did not yield sufficient products by polymerase chain reactions (PCR, not shown). This is in line with recent reports indicating that injected cells can be detected only for a short period of time after application . In contrast, in our study many MSCs remained at the spot of application and wasted, possibly by factor deprivation.…”
Section: Discussionsupporting
confidence: 93%
“…An optimal dispersion of the cells is important for the outcome of such therapies. Recent studies suggested that MSCs injected in muscular tissues may migrate and leave the injection site over time . In our study neo‐vascularization was not observed in the area of cell injection in any of the animals investigated, although MSC may facilitate neovascularization …”
Section: Discussioncontrasting
confidence: 48%
“…Agrawal, et al (2014) showed that hADSCs transplanted into subcutaneous and inguinal fat pad do not persist for longer than 3 weeks (90% reduction in cells number by day 10) in immunocompromised mice, while the clearance rate for immunocompetent recipients is faster. Of note, short survival time was associated with macrophage infiltration even in immunodeficient mice . Results from our laboratory indicate that hADSCs were still present in the gastrocnemius muscles of the injured limbs at 14 days after delivery …”
Section: Discussionmentioning
confidence: 82%
“…This is a major and original property of this new composite gel. Indeed, several in vivo studies, addressing the fate of biomaterial‐associated cells after their implantation, have revealed the loss of the majority of cells within 10–14 days (Agrawal et al, ). We assume that this behaviour is due to the composite gel capacity to by one side provide adhesion sites to cells, within the collagen matrix, while preventing cell migration, due to the GNF fraction.…”
Section: Discussionmentioning
confidence: 99%